Understanding petroleum reservoirs : towards an integrated reservoir engineering and geochemical approach - Cubitt, John M.; England, William A.; Larter, S. R. (Geological Society special publication ;, 2004)
Reservoir geochemistry can throw light on the origin of petroleum reservoir fluid heterogeneities at a variety of spatial and temporal scales. This information can be used to understand the formation and performance of petroleum accumulations, and is avaluable tool for exploration, development and production strategies.